Process-Oriented Guided-Inquiry Learning Model and Critical Thinking Ability of Elementary School Students - Via Yustitia; Melia Anggraini; Dian Kusmaharti; Petrus Jacob Pattiasina; Luluk Faridah (Jurnal Pendidikan dan Pengajaran, 2023)
The ability to think critically in learning mathematics still needs to be improved. It is caused by several factors and student errors in solving math problems. This study aims to determine the effect of the process-oriented guided-inquiry learning model on students' critical thinking skills on the circumference and area of a rectangle. This type of research is experimental with a post-test-only control group design. The population of this study was fourth-grade students consisting of 3 classes. Through random cluster sampling, two samples were selected: class IVc with 24 students as the experimental class and class IVb with 25 as the control class. The research data was obtained using the test method. The instrument used is a test sheet. The data analysis technique used is the normality test, homogeneity test, and t-test. The research used the help of the SPSS Version 26 program. The study results showed an effect of Process Oriented Guided-Inquiry Learning on the critical thinking skills of fourth-grade students on the perimeter and area of a rectangle. With these findings, the researcher recommends using the Process Oriented Guided-Inquiry Learning model to improve critical thinking skills.